Vegetation greenness and photosynthetic phenology in response to climatic determinants - Dang, Chaoya; Shao, Zhenfeng; Huang, Xiao; Zhuang, Qingwei; Cheng, Gui; Qian, Jiaxin (Frontiers in Forests and Global Change, 2023)
Vegetation phenology is a key indicator of vegetation-climate interactions, interannual vegetation productivity and carbon sink changes in terrestrial ecosystems. Therefore, it is very important to understand the temporal and spatial variability of vegetation phenology and the driving climatic determinants (e.g. temperature (Ts) and soil moisture (SM)). Vegetation greenness and photosynthetic phenology refer to double logistic (DL) method-extracted enhanced vegetation index (EVI) and solar-induced chlorophyll fluorescence (SIF) spring and autumn phenology, respectively. The growing season length (GSL) of greenness phenology (100 days) extracted based on EVI was longer than GSL of photosynthetic phenology (80 days) extracted based on SIF. Although their overall spatio-temporal pattern trends were consistent, some differences in spatial patterns existed. In addition, SIF-based photosynthetic phenology and EVI-based greenness phenology showed consistent factors of drivers, but differed to some extent in spatial patterns and the most relevant preseason dates. Spring photosynthetic phenology was mainly influenced by pre-season mean cumulative Ts (about 90 days). However, greenness phenology was controlled by both pre-seasons mean cumulative Ts ((about 55 days) and mean cumulative SM (about 40 days)). Autumn photosynthetic phenology was controlled by both periods mean cumulative Ts ((about 20 days) and SM (about 20 days)), but autumn greenness phenology was mainly influenced by pre-season mean cumulative Ts (85 days). The comparison analysis of SIF and EVI phenology helps to understand the difference between photosynthetic phenology and greenness phenology at regional scale.